GENDER INEQUALITY IN SOCIAL ECONOMIC FISHERMEN FAMILIES IN MALANG RAPAT VILLAGE GUNUNG KIJANG DISTRICT, BINTAN REGENCY, KEPULAUAN RIAU PROVINCE - Monica Simorangkir; Firman Firman; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Researchon Gender Inequality in the Fishermen's Family Socio-Economy was conducted in May 2018 in the Malang Rapat Village of GunungKijang District, Bintan Regency, Kepulauan Riau Province. This study was aimed to describe the access to property rights between husband and wife fishermen, analyze gender inequality in the education of boys and girls in fishermen's families, and analyze gender inequality in the outpouring of work time for fishermen's families. The method used in this research is survey method with a qualitative approach that was analyzed using Harvard analysis and the number of respondents in this study were 35 respondents with 3 informants.From the results of the research analysis, it was found that the ownership of assets in the name of the husband and access to dominant assets in the husband is due to the one who works for a living and the head of the family is the husband. Boys education takes precedence over girls because boys have a big responsibility to their families later while girls will eventually marry and become housewives.Wife's activity is heavier than that of a husband with more work time compared to his wife's husband. Based on the Harvard analysis, it can be known the division of labor and access control in the fishermen's family.Keywords: gender, inequality, Harvard analysis